Learners' Perceptions and Participation in Digital-Based Learning: A Review of the Effectiveness of Teaching Materials and Worksheets - Nur Hakima Akhirani Nasution; Silfa Hafizah Pulungan; Yusniar Harahap (Postgraduate, University of Mataram, 2023)
Technological developments and global changes that occur very quickly require academic practitioners to be adaptive and innovative in the learning process. Digital-based teaching materials are one answer that is expected to help teachers carry out the learning process in the classroom. This research aims to measure students' perceptions and participation in digital-based learning where researchers want to see the effectiveness of the teaching materials and worksheets used. This research uses a descriptive quantitative approach by collecting data through questionnaires which will be distributed to respondents consisting of 18 students in class IX of SMP N 1 Barumun Baru Padang Sidumpuan. The research results obtained show that student perceptions are in a very high category and student participation in digital-based learning is also in the high category. Therefore, according to students, the use of digital teaching materials, especially Powton teaching materials and live worksheets, is effective in classroom learning.